Unveiling the potential of spirulina algal extract as promising antibacterial and antibiofilm agent against carbapenem-resistant Klebsiella pneumoniae: in vitro and in vivo study - Mohamed I. Selim; Tarek El-banna; Fatma Sonbol; Walaa A. Negm; Engy Elekhnawy (Microbial Cell Factories)
Abstract Carbapenem-resistant Klebsiella pneumoniae poses a severe risk to global public health, necessitating the immediate development of novel therapeutic strategies. The current study aimed to investigate the effectiveness of the green algae Arthrospira maxima (commercially known as Spirulina) both in vitro and in vivo against carbapenem-resistant K. pneumoniae. In this study, thirty carbapenem-resistant K. pneumoniae isolates were collected, identified, and then screened for their susceptibility to several antibiotics and carbapenemase production genes using PCR. Both bla KPC and bla OXA-48 genes were the most predominant detected carbapenemase genes in the tested isolates. The phytochemical profiling of A. maxima algal extract was conducted using LC–MS/MS in a positive mode technique. The minimum inhibitory concentrations (MIC) of the algal extract ranged from 500 to 1000 µg/mL. The algal extract also resulted in decreasing the membrane integrity and distortion in the bacterial cells as revealed by scanning electron microscope. The bioactive compounds that were responsible for the antibacterial action were fatty acids, including PUFAs, polysaccharides, glycosides, peptides, flavonoids, phycocyanin, minerals, essential amino acids, and vitamins. Moreover, A. maxima algal extract revealed an antibiofilm activity by crystal violet assay and qRT-PCR. A murine pneumonia model was employed for the in vivo assessment of the antibacterial action of the algal extract. A. maxima showed a promising antibacterial action which was comparable to the action of colistin (standard drug). This was manifested by improving the pulmonary architecture, decreasing the inflammatory cell infiltration, and fibrosis after staining with hematoxylin and eosin and Masson’s trichrome stain. Using immunohistochemical investigations, the percentage of the immunoreactive cells significantly decreased after using monoclonal antibodies of the tumor necrosis factor-alpha and interleukin six. So, A. maxima may be considered a new candidate for the development of new antibacterial medications. Graphical Abstract